Below-elbow cast sufficient for treatment of minimally displaced metaphyseal both-bone fractures of the distal forearm in children: long-term results of a randomized controlled multicenter trial. (4th July 2021) - Musters, Linde; Diederix, Leon W; Roth, Kasper C; Edomskis, Pim P; Kraan, Gerald A; Allema, Jan H; Reijman, Max; Colaris, Joost W
Abstract : Background and purpose — We have previously shown that children with minimally displaced metaphyseal both-bone forearm fractures, who were treated with a below-elbow cast (BEC) instead of an above-elbow cast (AEC), experienced more comfort, less interference in daily activities, and similar functional outcomes at 7 months' follow-up (FU). This study evaluates outcomes at 7 years' follow-up. Patients and methods — A secondary analysis was performed of the 7 years' follow-up data from our RCT. Primary outcome was loss of forearm rotation compared with the contralateral forearm. Secondary outcomes were patient-reported outcome measures (PROMs) consisting of the ABILHAND-kids and the DASH questionnaire, grip strength, radiological assessment, and cosmetic appearance. Results — The mean length of FU was 7.3 years (5.9–8.7). Of the initial 66 children who were included in the RCT, 51 children were evaluated at long-term FU. Loss of forearm rotation and secondary outcomes were similar in the 2 treatment groups. Interpretation — We suggest that children with minimally displaced metaphyseal both-bone forearm fractures should be treated with a below-elbow cast.